Global Marine Ecosystem Response to a Strong AMOC Weakening Under Low and High Future Emission Scenarios - A. A. Boot; J. Steenbeek; M. Coll; A. S. von derHeydt; H. A. Dijkstra (Earth's Future)
Abstract Marine ecosystems provide essential services to the Earth System and society. These ecosystems are threatened by anthropogenic activities and climate change. Climate change increases the risk of passing tipping points; for example, the Atlantic Meridional Overturning Circulation (AMOC) might tip under future global warming leading to additional changes in the climate system. Here, we look at the effect of an AMOC weakening on marine ecosystems by forcing the Community Earth System Model v2 (CESM2) with low (SSP1‐2.6) and high (SSP5‐8.5) emission scenarios from 2015 to 2100. An additional freshwater flux is added in the North Atlantic to induce an extra weakening of the AMOC. In CESM2, the AMOC weakening has a large impact on phytoplankton biomass and temperature fields through various mechanisms that change the supply of nutrients to the surface ocean. We drive a marine ecosystem model, EcoOcean, with phytoplankton biomass and temperature fields from CESM2. In EcoOcean, we see negative impacts in Total System Biomass (TSB), which are larger for high trophic level organisms. On top of anthropogenic climate change, TSB decreases by −3.78% and −2.03% in SSP1‐2.6 and SSP5‐8.5, respectively due to the AMOC weakening. However, regionally and for individual groups, the decrease can be as large as −30%, showing that an AMOC weakening can be very detrimental for local ecosystems. These results show that marine ecosystems will be under increased threat if the AMOC weakens which might put additional stresses on socio‐economic systems that are dependent on marine biodiversity as a food and income source.